2007
DOI: 10.1021/ja0730361
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Vibrational Analysis, and Insights into Host−Guest Interactions in As-Synthesized Pure Silica ITQ-12 Zeolite by Periodic B3LYP Calculations

Abstract: As-made and calcined ITQ-12 zeolites are structurally characterized by means of the analysis of their vibrational modes. The experimental IR spectra made on high crystalline samples are compared with accurate B3LYP periodic calculations performed with the CRYSTAL06 code. The fair agreement between both sets of data allows us to make a reliable assignment of the IR modes. Thanks to the detailed information provided by the theoretical calculations, the analysis of the IR intensities, the Born dynamic charges, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 46 publications
8
64
1
Order By: Relevance
“…As in previous works by some of the present authors 24-29 the B3LYP Hamiltonian 30 was employed, that contains a hybrid Hartree-Fock/density-functional exchangecorrelation term, and is widely and successfully used in molecular quantum chemistry 31 as well as in solid state calculations, where it has been shown to reproduce vibrational frequencies in general good agreement with experiment. [32][33][34][35] The adopted basis set has already been used in a previous investigation of calcite (BSD in Ref. 36).…”
Section: Methodsmentioning
confidence: 99%
“…As in previous works by some of the present authors 24-29 the B3LYP Hamiltonian 30 was employed, that contains a hybrid Hartree-Fock/density-functional exchangecorrelation term, and is widely and successfully used in molecular quantum chemistry 31 as well as in solid state calculations, where it has been shown to reproduce vibrational frequencies in general good agreement with experiment. [32][33][34][35] The adopted basis set has already been used in a previous investigation of calcite (BSD in Ref. 36).…”
Section: Methodsmentioning
confidence: 99%
“…The second interaction is a characteristic H-bond with a HO distance of 1.83 Å. Concerning the F -anion, it moves out from the center of the cage, where it is located in the asmade samples, according to both experimental 1,4 and theoretical 7,8,28 evidence. The displacement of the fluoride anion, which in the original cage has barely enough room to reside inside the unit experimenting slight Pauli repulsion with the O electrons, 7,8,28 is now possible because the interaction of the O-bridging with the proton gives rise to a weakening of the SiO bond, in accordance with the Gutmann rules, 29 involving the lengthening of the bond and, therefore, the enlargement of the cage close to the Si angle.…”
Section: Computational and Modeling Detailsmentioning
confidence: 92%
“…1,2 At variance with the former that requires basic media, the latter is performed in neutral solutions (pH [5][6][7][8][9], and the presence of F -ions as mineralizing agents allows dealing with reaction mixtures with very low or even null Al content. Moreover, the products obtained in this manner exhibit a quite large crystal size and low occurrence of structural defects, which permits synthesizing significantly hydrophobic materials suitable for interesting technological applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 19 ] However, the rationale behind this effect and the apparent paradox that fl uoride would exert it precisely in cases in which there is less evidence for strong Si-F interactions in the fi nal material, i.e., when F is occluded in D4R, remained unexplained until the very recent works by Zicovich-Wilson, Camblor and coworkers. These authors fi rst showed that a signifi cant charge transfer between the guests (fl uoride and organic cations) and the silica host occurs [ 20 ] and then that the effect may effectively revert the order of stability of two silica frameworks. [ 21 ] This charge transfer increases the ionicity of the silica framework ( Figure 2 ), making it deviate from the model of rigid tetrahedra units and affording relaxation of otherwise strained units such as the D4R.…”
Section: Fluoride Encapsulationmentioning
confidence: 99%